A word with the rich (James 5:1-6) - Part II - Alana, Olu E. (Verbum et ecclesia, 2003)
This second and concluding part of this essay on "A word with the rich", focuses on the social and historical milieu of the Letter of James with a view to appreciating the cultural context giving rise to the apostrophe handed down on the rich by the author of the letter. The texts containing the apostrophe are examined and the challenges they pose to the rich are explored for recommendation to today’s rich.